Quality of services: the ultimate objective of regulation - Sundar, S.; Sarkar, S.K. (2000)
Regulatory reforms in India as in other countries seek to provide quality services to the consumer. This paper discusses the initiatives taken by regulators in developed countries such as U.K. and U.S. as well as developing countries such as Sri Lanka to set and enforce quality standards and ensure consumer satisfaction. The authors argue that although certain efforts have been initiated in India in the electricity, telecom and ports sectors to set quality standards, a lot more has to be done before consumers can begin to realize the benefits of regulatory reforms. They also stress he need for active consumer participation along with continuous vigilance by research institutions to make these benefits real. - Reproduced
Keywords: Quality control; Public utilities